THE SETTLEMENT OF SHARIA ECONOMIC DISPUTES IN INDONESIAN ISLAMIC CLASSIC TRADITIONS AND POSITIVE LAW - Adriandi Kasim (IAIN Manado, 2021)
Using a qualitative method with a sociological-normative approach, it was found that today's rapid development has caused various kinds of disputes. In this article, the author discusses sharia economic disputes and their resolution in the Islamic tradition and positive law in Indonesia to understand the problems of economic disputes and their resolution so that they can become knowledge and guidelines in conducting business transactions. The results of the discussion that the author obtained, namely sharia economic disputes, are disputes that occur in muammalah activities. This occurs in banking, non-banking, capital market, as well as the economy as a whole due to several factors such as default, tadlis, taghrir, or other things that can harm the rights of others. Settlement of disputes in Islamic law, namely sulh and tahkim. As for the applicable law in Indonesia, namely peace both by litigation and non-litigation, ADR, and arbitration includes BANI, BASYARNAS and other arbitration institutions. In this case, the authors conclude that every community that will conduct business transactions requires the principle of prudence and there have been many legal attempts by the government in resolving these disputes.